Latitudinal distribution of OCPs in the open ocean atmosphere between the Argentinian coast and Antarctic Peninsula - Rimondino, Guido Noé; Pepino, Ana Julieta; Manetti, Martin Diego; Olcese, Luis Eduardo; Argüello, Gustavo Alejandro
Long-range atmospheric transport is one of the most important ways in which persistent organic pollutants can be transported from their source to remote and pristine regions. Here, we report the results of the first Argentinian measurements of organochlorine pesticides in the Antarctic region. During a 9665-km track onboard OV ARA Puerto Deseado, within the framework of Argentinian Antarctic Expeditions, air samples were taken using high-volume samplers and analyzed using GC-μECD. HCB, HCHs, and endosulfans were the major organic pollutants found, and a north-south gradient in their concentrations was evident by comparing data from the Argentinian offshore zone to the South Scotia Sea. Fil: Rimondino, Guido Noé. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Investigaciones en Físico-química de Córdoba. Universidad Nacional de Córdoba. Facultad de Ciencias Químicas. Instituto de Investigaciones en Físico-química de Córdoba; Argentina Fil: Pepino, Ana Julieta. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Investigaciones en Físico-química de Córdoba. Universidad Nacional de Córdoba. Facultad de Ciencias Químicas. Instituto de Investigaciones en Físico-química de Córdoba; Argentina Fil: Manetti, Martin Diego. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Investigaciones en Físico-química de Córdoba. Universidad Nacional de Córdoba. Facultad de Ciencias Químicas. Instituto de Investigaciones en Físico-química de Córdoba; Argentina Fil: Olcese, Luis Eduardo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Investigaciones en Físico-química de Córdoba. Universidad Nacional de Córdoba. Facultad de Ciencias Químicas. Instituto de Investigaciones en Físico-química de Córdoba; Argentina Fil: Argüello, Gustavo ...